Microstratigraphic Analysis of Fossil Distribution in the Lower Hornerstown and Upper Navesink Formations at the Edelman Fossil Park, NJ - Voegele, Kristyn K.; Ullmann, Paul V.; Lonsdorf, Tara; Christman, Zachary; Heierbacher, Michael; Kibelstis, Brian J.; Putnam, Ian; Boles, Zachary M.; Walsh, Shane; Lacovara, Kenneth J. (Frontiers in Earth Science, 2021)
Maastrichtian–Danian sediments of the Navesink and Hornerstown formations at the Jean and Ric Edelman Fossil Park of Rowan University in Mantua Township, New Jersey, have long intrigued paleontologists. Within the basal Hornerstown Formation occurs the Main Fossiliferous Layer (MFL), a regionally well-known and diverse bonebed. The lithostratigraphic and chronostratigraphic position of this fossil layer have been debated for more than 50 years, fueling debate over its origin. Herein, we present the results of a microstratigraphic analysis of the fossil composition and distribution of the MFL undertaken to rectify these discrepancies. Through methodical top-down excavation, we recorded the three-dimensional position of every fossil encountered. Three-dimensional visualization and analyses of these data in ArcGIS Pro yielded an unprecedented view of this bonebed. Most reported discrepancies about the stratigraphic placement and thickness of the MFL can be explained by the presence of two distinct fossil assemblages within this interval that are occasionally combined into a single bonebed. The stratigraphically-lower assemblage, herein termed an “oyster layer”, is geometrically-tabular and exhibits low taxonomic diversity, high abundance of the oyster Pycnodonte, and moderate taxonomic richness. The stratigraphically-higher assemblage, the MFL, occurs approximately 9 cm higher in section and exhibits high values of taxonomic diversity, fossil abundance, and taxonomic richness. Sedimentological homogeneity throughout this interval suggests that these faunal contrasts arise from the two assemblages having formed via independent taphonomic pathways. Specifically, prevalence of Pycnodonte in the oyster layer implies formation by a selective mortality event, whereas the diversity of the MFL appears to reflect a more universal agent of mortality. Spatial variations in the stratigraphic distribution of fossils within the MFL in our excavation area indicate this assemblage does not form a simple, tabular layer as previously thought and may, in part, record original bathymetry. Importantly, our definition of the MFL and detailed characterization of its stratigraphic placement are essential for future studies on the taphonomic origin and chronostratigraphy of this bonebed. Universal use of this definition would allow researchers to confidently elucidate the exact lithostratigraphic positions of precise chronostratigraphic indicators within the MFL and accurately estimate the degree of time averaging of its fossils.